2017
DOI: 10.1093/rpd/ncw384
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Influence of the Position Inside a Small Aircraft on the Cosmic-Radiation-Induced Dose

Abstract: This article report the measurements on-board a small aircraft at the same altitude and around the same geographic coordinates. The measurements of Ambient Dose Equivalent Rate (H*(10)) were performed in several positions inside the aircraft, close and far from the pilot location and the discrimination between neutron and non-neutron components. The results show that the neutrons are attenuated close to fuel depots and the non-neutron component appears to have the opposite behavior inside the aircraft. These e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The aircraft model was made in a simple way and consists of 58 cells and 12 different materials to describe its structure, material, and occupants. The geometry of the aircraft is detailed in a previous work [17] which demonstrates the validity of the simulations by comparing the ambient dose equivalent rate given by the aircraft Monte Carlo simulation results with experimental data taken in flight. From the results of this previous work, we found that the experimental and simulated results are in good agreement within 3%, evidencing that, although the aircraft model was built simply, the set represented by the aircraft model and the methodology of the atmosphere radiation source is a good way to represent reality.…”
Section: A Model Of the Aircraftmentioning
confidence: 93%
See 2 more Smart Citations
“…The aircraft model was made in a simple way and consists of 58 cells and 12 different materials to describe its structure, material, and occupants. The geometry of the aircraft is detailed in a previous work [17] which demonstrates the validity of the simulations by comparing the ambient dose equivalent rate given by the aircraft Monte Carlo simulation results with experimental data taken in flight. From the results of this previous work, we found that the experimental and simulated results are in good agreement within 3%, evidencing that, although the aircraft model was built simply, the set represented by the aircraft model and the methodology of the atmosphere radiation source is a good way to represent reality.…”
Section: A Model Of the Aircraftmentioning
confidence: 93%
“…Each source built on MCNPX has a different FNF factor and depends on the number of neutrons obtained by gPartAt, which was originated from the primary protons and alphas from cosmic radiation incidents at the top of the atmosphere. The explanations of this equation and the FNF factor are given in previous work [17]. Fig.…”
Section: ̇= × 2 × ×mentioning
confidence: 98%
See 1 more Smart Citation
“…In SEU, by using an error correcting code it is easier to fix a software issue however when MBU is considered, it is not as straight forward as SEU. For full recovery, the system needs to be restarted (Prado, 2013) (Maniatakos, 2012) (Australian Transport Safety Bureau, 2008) that is reported. In the report, SEE is given as the most probable reason for such a damage.…”
Section: Vulnerability and Mitigation Strategiesmentioning
confidence: 99%